The Diagnostic Accuracy of Automated Immature Granulocyte Percentage (IG%) for Early Sepsis and Serious Bacterial Infection Detection in Emergency Department Patients: A Systematic Review of Diagnostic Test Accuracy Studies - Hendra Dwitanto; Nina Amelinda Panggabean (The Indonesian Journal of General Medicine, 2025)
Introduction Sepsis, defined as a life-threatening organ dysfunction resulting from a dysregulated host response to infection (Singer et al., 2016), demands rapid diagnostic tools in the Emergency Department (ED). The automated Immature Granulocyte percentage (IG%), derived from routine Complete Blood Count (CBC), represents a real-time, cost-effective marker of acute hematopoietic stress, historically recognized as the 'left shift' (Ayres et al., 2019). The timely quantification of IG% offers a potentially superior advantage over traditional inflammatory markers with slower kinetic profiles (Bhansaly et al., 2022). Methods A systematic review of diagnostic test accuracy (DTA) studies was performed following the methodological standards of the PRISMA-DTA guidelines. Studies evaluating IG% in acute care settings (ED, ICU) with sufficient data for 2x2 contingency tables were included. Methodological quality and risk of bias were meticulously assessed using the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) tool (Whiting et al., 2011). Pooled estimates for diagnostic metrics, including Sensitivity, Specificity, and the Diagnostic Odds Ratio (DOR), were calculated using a robust bivariate random effects model to account for study heterogeneity. Results A total of 15 high-quality diagnostic accuracy studies were included in the quantitative synthesis, encompassing diverse patient spectrums and rigorous sepsis/Serious Bacterial Infection (SBI) definitions. The meta-analysis demonstrated highly significant diagnostic performance for IG%. The pooled diagnostic accuracy yielded an Area Under the Curve (AUC) of 0.86 (95% CI: 0.83–0.89). The pooled Sensitivity was calculated at 83.1% (95% CI: 78.5%–87.1%), and pooled Specificity at 85.5% (95% CI: 82.1%–88.6%). Furthermore, IG% demonstrated a robust pooled DOR of 31.2 (95% CI: 22.5–43.1), significantly surpassing most traditional ED biomarkers like Lactate (DOR 4.78) (Bhansaly et al., 2022; Wong et al., 2017). Importantly, Immature Granulocyte Count (IG%) and IG% showed discriminatory value (AUC \sim 0.82) as early as 24 hours prior to clinical diagnosis, demonstrating a crucial temporal advantage over Procalcitonin (PCT) (Bhansaly et al., 2022). Discussion The high pooled DOR confirms IG% as an essential ancillary biomarker for rapid sepsis triage. Its strength lies in its immediate availability, which circumvents the turnaround delays associated with specialized inflammatory assays. Observed heterogeneity in optimal cutoff values, ranging from 0.2% to 3.0%, reflects the dependency on patient age (adult versus pediatric) and clinical objective (screening versus exclusion) (Buoro et al., 2015; Zhong et al., 2021; Ayres et al., 2019). The integration of IG% into multivariate prediction models, particularly alongside C-Reactive Protein (CRP) and White Blood Cell (WBC) count, achieved the highest reported sensitivity of 93.0% for SBI detection (Kwon et al., 2017). Conclusion Automated IG% is a rapid, inexpensive, and highly effective biomarker for the early detection and risk stratification of sepsis and SBI in the ED. Its combination of high diagnostic accuracy, cost-effectiveness, and critical temporal superiority provides clinicians with a powerful tool for initiating timely, goal-directed therapy and improving outcomes in acute emergency settings.